Modified xiaoyao san combined with chemotherapy for breast cancer: A systematic review and meta-analysis of randomized controlled trials - Pan, Junhua; Fu, Shunlian; Zhou, Qian; Lin, Dajun; Chen, Qiu (Frontiers in Oncology, 2023)
Due to the 350-word limit, i had to cut out a lot. please read the manuscript. Thanks a lot. Background: Breast cancer is the most common malignancy in women and the leading cause of cancer death worldwide. Chemotherapy plays an imperative role in the conventional treatment of breast cancer, whereas it also imposes some physical burdens on cancer patients. Consequently, more and more patients turn to seek the assistance of Complementary and Alternative Medicine, particularly traditional Chinese medicine (TCM). Xiaoyao san (XYS), a classical TCM formula, is commonly prescribed to improve breast cancer in China and achieves satisfactory effects. An increasing number of studies suggest that comparing chemotherapy alone, Chinese herbal medicine combined with chemotherapy is more dominant, which can not only enhance efficacy but also reduce toxicity caused by chemotherapy. At present, some experimental results demonstrate that several of the components in XYS can stop breast cancer tumor cells from growing. The efficacy of this combined treatment for breast cancer, however, has not been thoroughly evaluated. The safety and side-effects of it yet remain unclear as well. Therefore, this study is urgently needed to assess its efficacy and safety against breast cancer in depth. Methods: Eight databases were searched by us for randomized controlled trials from their inception until April 3, 2022. Randomized controlled trials (RCTs) comparing modified XYS in combination with chemotherapy versus chemotherapy alone were included. Software Review Manager (version 5.4.1) and Cochrane Collaboration “risk of bias” tools were used for meta-analysis and assessment of the risk of bias. Results: A total of 17 RCTs involving 1207 patients were identified for analysis. The results of this meta-analysis revealed that modified XYS combined with chemotherapy can benefit breast cancer patients. None of the included studies identified any adverse side effects. Modified XYS combined with chemotherapy can improve the short-term efficacy of solid tumors, improve QOL (quality of life) of breast cancer patients, relieve the patients' clinical symptoms, reduce the incidence of depression, improve the decline of leukocytes and platelets, reduce the occurrence of nausea and vomiting, reduce cardiotoxicity of patients,